Application of Jigsaw-Type Cooperative Learning Model in Improving Short Story Writing Learning in Grade VIII Students at Junior High School - Amalia; Hasnur Ruslan; Andi Bismawati; Sukma; Asrianti (Universitas Islam Negeri Palopo, 2025)
This study aims to improve the ability to write short stories for grade VIII students of SMP Negeri 5 South Banawa through the application of a Jigsaw-type cooperative learning model. The background of this research departs from the low ability of students to write short stories, which is caused by a lack of interest, imagination, and the application of a learning model that is still teacher-centered. The type of research used is quantitative research with a descriptive method. The research subjects consisted of 13 grade VIII students of SMP Negeri 5 Banawa Selatan for the 2025/2026 school year. Data collection techniques are carried out through observation, documentation, and tests (pre-test and post-test). The results of the study showed an increase in short story writing skills after the application of the Jigsaw-type cooperative learning model. The average score of the students was 51.07, while the average score of the post-test increased to 80.98. The results of the t-test analysis showed that the calculated t-value of 10.55 was greater than the t-table of 1.782 with a significant level of 0.05, so the research hypothesis was accepted. Thus, the application of the Jigsaw-type cooperative learning model has a significant effect on improving the ability to write short stories for grade VIII students of SMP Negeri 5 South Banawa.